Commercial leases in Australia - Duncan, W. D. [ (William David)] (Lawbook Co., 2008)
Covers all aspects of commercial leases, not only retail shops but also all types of office and industrial leases. This new edition incorporates new practical precedent material such as precedent agreement clauses, and case studies that are all extensively annotated and commented upon